Characterization of surface layer development on duplex stainless steel resulting from thermochemical hybrid treatment / Mohd Shahriman Adenan - Adenan, Mohd Shahriman (Institute of Graduate Studies, UiTM, 2015)
The application of duplex stainless steels in various applications such as in petrochemical, water desalination and paper milling industries has rapidly increased in recent years, taking advantage of the combination of high strength and good corrosion resistance from the dual phase stainless steels. However, having low wear resistance and low surface hardness limits the applicability of the steels for wider applications; thus, improvement of the features is essential. A thermochemical hybrid treatment process has been developed to improve the wear resistance and surface hardness of duplex stainless steels without compromising its corrosion resistance. The process was performed by using a Faculty of Mechanical Engineering 8 mixture of methane (CH4), ammonia(NH3) and nitrogen (N2) at low temperature of below 500°C…